2016
DOI: 10.1016/j.otsr.2015.10.001
|View full text |Cite
|
Sign up to set email alerts
|

May one-stage exchange for Candida albicans peri-prosthetic infection be successful?

Abstract: Level IV-Historical cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 15 publications
0
9
0
3
Order By: Relevance
“…From the patients treated with resection arthroplasty, one dead after fluconazole treatment 34, two suffered amputation 14, 23 and two were found to have a bacterial infection 26, 56. All three patients treated with one-stage exchange arthroplasty cured 40, 45. Our two patients are currently well with antifungal treatment only, and no relapse of disease has been observed in the short follow-up.…”
Section: Literature Reviewmentioning
confidence: 67%
See 2 more Smart Citations
“…From the patients treated with resection arthroplasty, one dead after fluconazole treatment 34, two suffered amputation 14, 23 and two were found to have a bacterial infection 26, 56. All three patients treated with one-stage exchange arthroplasty cured 40, 45. Our two patients are currently well with antifungal treatment only, and no relapse of disease has been observed in the short follow-up.…”
Section: Literature Reviewmentioning
confidence: 67%
“…Moreover, some authors have recently reported favourable outcome after one-stage exchange in selected cases of fungal PJI 45, 74. In these cases, the responsible microorganism was identified post-operatively, with delayed specific antifungal treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Esta indicação é baseada em relatos e séries de casos e opinião de especialistas. Relatos de remissão clínica com a limpeza cirúrgica e retenção do implante (16,45,47,48,61) , com a revisão em um tempo (46,59,68,70) e até com tratamento conservador sem abordagem cirúrgica (16,43) já foram publicados.…”
Section: Discussão Dos Resultados Da Série De Casosunclassified
“…foi utilizado em inúmeros casos. (16,19,31,34,37,40,42,46,49,51,56,57,60,68,70) . A revisão dos casos realizada neste trabalho não encontrou benefício nesta prática e a associação de antifúngicos não é mencionada como possibilidade terapêutica nos principais Guidelines que versam sobre infecção em prótese articular (21,28,29) .…”
Section: Discussão Dos Resultados Da Série De Casosunclassified